Weed dynamics and management in conservation agriculture: challenges and way forward - Das, T. K.; Sharma, A. R.; Yaduraju, N. T.; Nath, C. P. (Indian Farming, 2018)
The levels of disturbance in habitat (tillage, mulching, fire, flooding, drought etc.) and changes made in the agronomic practices towards raising a crop may lead to changes in weed species over time. Weeds are ubiquitous, having a widerange of ecological amplitude that determines their adaptability. Conservation agriculture is a paradigm shift from conventional mode of agriculture. Continuous residue cover and no/minimal disturbance of soil under conservation agriculture provides specific micro-climate for weeds in crop fields and herbicide continues to be the sole option for weed control. Weed management remains crucial under zero-till residue-laden conditions. Application of higher dose of herbicides, granular formulations, non-selective herbicide during off-season, high volume rate for pre-emergence herbicide application and preferential application of post-emergence herbicides are required to increase the herbicide efficacy under conservation agriculture. However, an integrated weed management practice involving tillage, residue, cover crops, intercrops, herbicides would go a long way towards efficient weed management under Conservation agriculture.